A rare case of double orifice mitral valve: A case report - Shweta S Kandpal; Anil Kumar; Manisha Mishra; Yatin Mehta (Annals of Cardiac Anaesthesia, 2021)
Double-orifice mitral valve is a rare congenital anomaly being associated with other cardiac defects and rarely presented in isolation. Valve function can be preserved for long and it is usually an incidental finding. We present an unusual case of double-orifice mitral valve with mitral regurgitation in a middle-aged man associated with the atrial septal defect, highlighting the role of three-dimensional transesophageal echocardiography.